1974
DOI: 10.1159/000224983
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Stress on Lesion Growth and on Survival of Animals Bearing Parenteral and Intracerebral Leukemia L1210 and Walker Tumors

Abstract: Rats with Walker tumor injected intramuscularly in both hind legs and subjected to forced swimming for 15 min daily for 10 days displayed a trend toward decreased lesion size, especially in older intact animals as compared to unexercised intact or bilaterally adrenalectomized controls. Secondary tumor nodules occurred at the lower abdominal or inguinal areas and appeared to be more extensive in the older exercised rats. The survival rates offorced exercised rats bearing Walker tumor cortically did not differ s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

1975
1975
1989
1989

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 11 publications
0
21
0
1
Order By: Relevance
“…It should be noted, however, that although we previously found that 10 inescapable shock sessions had effects that went beyond simply blocking the acute stress-induced tumor enhancement and actually inhibited tumor growth relative to nonshocked controls such an effect was not evident in the present experiment. This is not entirely surprising, in view of the fact that the inhibition we previously observed was quite small and the chronic stress regimens typically employed in studies reporting inhibited tumor growth are considerably more extensive (see [30][31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: Methodsmentioning
confidence: 77%
See 3 more Smart Citations
“…It should be noted, however, that although we previously found that 10 inescapable shock sessions had effects that went beyond simply blocking the acute stress-induced tumor enhancement and actually inhibited tumor growth relative to nonshocked controls such an effect was not evident in the present experiment. This is not entirely surprising, in view of the fact that the inhibition we previously observed was quite small and the chronic stress regimens typically employed in studies reporting inhibited tumor growth are considerably more extensive (see [30][31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: Methodsmentioning
confidence: 77%
“…While such an hypothesis might account for the fact that chronic shock following tumor cell transplantation eliminated the effects of acute shock on tumor growth, it is clear that the actual inhibition of tumor growth observed previously (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) cannot be adequately accounted for by these formulations. That is to say, the fact that tumor growth was retarded relative to nonstressed mice in these earlier studies points to effects other than, or in addition to, the elimination of the acute shock effect.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Kelly et al (9) reported that neurological signs for an expanding cerebral tumor in Rhesus monkeys comprise dilation of pupils, blindness, enlargement of skull, muscular rigidity, spasm and paralysis with death generally following soon after. Brain anatomic changes and survival of animals with brain implants of ascites tumor suspensions of varying cell number (6,7) and hydrocarbons (5) have been advanced by this laboratory. The present study expands the latter reports with the view of eluci dating the behavior of such animals when subjected to psychological parameters.…”
Section: Introductionmentioning
confidence: 99%